2017
DOI: 10.1503/cjs.008616
|View full text |Cite
|
Sign up to set email alerts
|

The burden of second hip fractures: provincial surgical hospitalizations over 15 years

Abstract: The burden of second hip fractures: provincial surgical hospitalizations over 15 years Background: Second hip fractures account for up to 15% of all hip fractures. We sought to determine if the proportion of hip fracture surgeries for second hip fracture changed over time in terms of patient and fracture characteristics. Methods:We reviewed the records of patients older than 60 years hospitalized for hip fracture surgery between 1990 and 2005 in British Columbia. We studied the proportion of surgeries for seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Analysis of our data showed that the incidence of contralateral femoral fractures was 9.56%. This reflects findings from several previous studies in the literature [ 5 , 17 , 18 ]. The median time between the first and contralateral hip fracture was three years.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of our data showed that the incidence of contralateral femoral fractures was 9.56%. This reflects findings from several previous studies in the literature [ 5 , 17 , 18 ]. The median time between the first and contralateral hip fracture was three years.…”
Section: Discussionsupporting
confidence: 90%
“…In any case, the risk of second fracture is highest in the first months after the initial fracture and decreases thereafter [241], and seems to be shorter among patients who had suffered complications during the initial episode [246]. An increase in the rate of second hip fractures increased from 1990 to 2005 was observed in Canada [233], but decreased by 10% annually between 1999 -2009 in Spain [232], while it remained stable in the United Kingdom [240].…”
Section: Second Hip Fracturementioning
confidence: 93%
“…Approximately one third of patients with hip fractures have suffered another fragility fracture previously [228]. 7 -15% of patients admitted have a second hip fracture [229][230][231][232][233][234][235][236], with an accumulated incidence of 1.2 -3% in the first year and 9-10% at 8 years [7,[237][238][239][240][241][242][243][244], and can reach over 20% among patients with Alzheimer's disease [245]. Time between hip fracture varies upon study methodology and observation period; some authors state that over half of these occur in the first year after fracture [230,238] while other suggest the median time between hip fractures is over 3 years [232,236].…”
Section: Second Hip Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…With better vertebral fracture detection and response to an initial FF, hip fractures can be prevented, with a cost savings of about $27 000 per fracture in direct costs in hospital and in the year after surgery. 37 In addition, the assessment and treatment arms of care can be addressed through the role of nurse-led clinics, supervised by an orthogeriatrician, as done in Australia and the UK. By having a dedicated health care practitioner, specialized care tailored to patients with FFs can be delivered.…”
Section: Future Directionsmentioning
confidence: 99%